Stability Analysis for Grain Quality Parameters among the Mutants of ADT(R) 47 Rice (Oryza sativa) - T, Radhamani; Sassikumar, D.; Packiaraj, D.; Veni, K. (International Journal of Bio-resource and Stress Management, 2023)
Induced mutagenesis was done in the seeds of ADT(R) 47 rice variety with different doses of gamma rays (150 Gy, 200 Gy, 250 Gy and 300 Gy) and EMS (80 mM, 100 mM, 120 mM and 140 mM) at Tamil Nadu Rice Research Institute, Aduthurai during 2012. An experiment was conducted during 2015 at four environments namely, Aduthurai (E1), Thanjavur (E2), Tirur (E3) and Madurai (E4) to assess the stability of thirteen different grain quality traits among the 16 mutants of the rice variety ADT (R) 47 rice (Oryza sativa L.). ANOVA of Eberhart and Russell revealed that, performance of different mutant lines fluctuated significantly from their respective linear path of response to environment. Most of the grain quality parameters showed non-significant mean squares except gel consistency and amylose percentage indicating the influence of genotype×environment (G×E) interactions on these two grain quality measures. The environmental indices for the expression of the traits revealed that Thanjavur is favourable for linear elongation ratio and amylose content. Tirur was favourable for the traits viz., hulling percentage, milling percentage, head rice recovery percentage, kernel length, kernel breadth, kernel length after cooking, breadth after cooking, gel consistency and volume expansion ratio whereas Madurai was favourable for L:B ratio and breadthwise expansion ratio. From the overall assessment, the mutant 200-21-1 was identified to possess desirable head rice recovery percentage and cooking qualities along with stable yield. These mutant was declared stable in expression of trait through Eberhart and Russell model, hence identified as the best mutant for promotion as variety.